CHARACTERISTICS AND SUBSTANTIATION OF THE USE OF PELLETS AS A MODERN DOSAGE FORM ON THE MARKET OF UKRAINE - Yerkhova , Anna; Katynska , Maryna (The Ukrainian Scientific Medical Youth Journal, 2021)
currently, omeprazole pellets are one of the most common pellet formulations on the pharmaceutical market of Ukraine (Gorobets, Matyash, Pekhenko & Barna, 2019). This medication is available in capsule form. Pellets are multi particular dosage forms that have several advantages over monoparticular dosage forms; therefore, pellets are promising oral delivery systems for active pharmaceutical ingredients (APIs). Pellets are used when the stability of the active substance changes with fluctuations in the pH of the environment, when irritation of the gastric mucosa is possible, to facilitate swallowing (especially important for patients with dysphagia, elderly patients, and children). When using polymers in the shell, it is possible to regulate the release in a certain part of the gastrointestinal tract, this allows you to get a point pharmacological effect. In addition, pellets can be of different sizes (from 0.1 to 2 mm), because of their shape, pellets exhibit abrasion resistance and are more fluid. Omeprazole is a synthetic substance. The active ingredient suppresses gastric acid secretion. In refers to the pharmaceutical group of proton pump inhibitors, it prescribes drugs in this group to treat active duodenal ulcers, gastric ulcers, gastro-oesophageal reflux disease (GERD), severe erosive esophagitis, pathological hypersecretory conditions, for example, Zollinger Ellison syndrome. Among the most commonly used methods for the production of pellets are: stage-by-stage spraying of solutions or suspensions (the second name is stage-by-stage layering); direct pelletization (the second name is extrusion-spheronization); spray drying and spray cooling of melts; agglomeration-spheronization. Unfortunately, at the moment, none of the Ukrainian manufacturers is manufactured enteric pellets on their own (they buy ready-made pellets), while there are medicines of both foreign and Ukrainian origin on the domestic market. The article contains an overview of pharmaceutical preparations as pellets, systematization of information on production methods, a review of omeprazole drugs as pellets, presented on the pharmaceutical market of Ukraine. The purpose of this study was to summarize the cases when the use of such a form as pellets is the most reasonable; make an overview of medicines in Ukraine containing pellets; summarize modern methods of pellet production.